Innovación y emprendimiento con bases tecnologicas en la construcción en Ecuador - Borja Chiriboga, Francisco Daniel (2020)
Technology-based enterprises (TBA) have become the basis of economic development in the world, so to understand conceptually and whether they really operate in the current context is a need that envisions the future of Ecuador, specifically in the area of construction, considering that at the moment no records of implementation and application have been found. Therefore, the objective of this research is to determine if EBT is being generated in Ecuador, in which institutions and in what phase they are located. For the methodological process, a set of interviews was conducted with 11 universities, two construction companies and one certification company. This information was processed through the qualitative analysis program ATLAS TI. The results showed that two universities at the country level basically fulfilled the requirements by 80%, in addition to the certifying company; in which their biggest shortcomings were the transfer of technology, the development of innovation and legal aspects; in the other institutions it was observed the non-existence of a market vision, the viability towards a patent or intellectual property and the commercialization analysis; the parameter of financing is fulfilled but it does not allow the institutions to establish the transfer to the market. Finally, it is concluded that in Ecuador there is no EBT in the construction area and it has an early development.